2021
DOI: 10.1021/acs.cgd.0c01714
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of CH4/CO2 Hydrate Phase Transitions in Sandstone Pores

Abstract: This paper reports the formation and dissociation pattern of hydrate crystals with varying compositions of CH4 and CO2 in porous media. Direct visualization was carried out using a high-pressure, water-wet, silicon wafer-based micromodel with a pore network resembling sandstone rock. Hydrate crystals were formed under reservoir conditions (P = 45–65 bar and T = 1.7–3.5 °C) from either a two-phase system consisting of liquid water and a CH4–CO2 gas mixture or a three-phase system consisting of liquid water, CH4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 33 publications
(52 reference statements)
1
28
0
Order By: Relevance
“…Further depressurization near the CO 2 stability pressure would lead to dissociation of the unstable mixed hydrate because the driving force is no longer sufficient, and the increase in the released water will not participate in the reformation process. 38…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further depressurization near the CO 2 stability pressure would lead to dissociation of the unstable mixed hydrate because the driving force is no longer sufficient, and the increase in the released water will not participate in the reformation process. 38…”
Section: Resultsmentioning
confidence: 99%
“…As the pressure inside the vessel moves through the different regions of hydrate stability, phase changes may occur, including dissociation and reformation of hydrates, which would lead to fluid migration and fluid redistribution, thus affecting the yield and storage potential. 38 Previous studies that focused on examining the pressure response curve during the shut-in period suggest three characteristic pressure responses during the degassing. 14 The first is a stable pressure curve during gas expansion; the second is an abrupt pressure drop followed by a rapid pressure rise at the onset of hydrate dissociation; and the third is a stable pressure after complete hydrate dissociation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrate morphology controls the total hydrate surface area, while the pore size distribution controls the hydrate stability. The pore-scale visualization studies have shown that hydrate remained stable in narrow pore throats outside of their stability zone [6,66]. In another study, the correlation of the size of the hydrate particles with self-preservation was investigated and the particle particles larger than 0.5 mm in diameter showed a high degree of self-preservation [67].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The presence of additives and substrate wettability also play a role in hydrate growth [38][39][40]. The most complex configurations observed so far by optical microscopy are those obtained in etched twodimensional silica glass or silicon wafer micromodels [50][51][52] or by using lab-on-a-chip technology [53][54][55].…”
Section: Introductionmentioning
confidence: 99%